The Effectiveness of Behavioral Contract Techniques in Addressing Smoking Among Students in School Settings - Laura Amelia; Ridwan Syahran; Munifah Munifah; Nur Eka Wahyuningsih Riyadi (Journal of Educational Sciences, 2026)
Smoking behavior among Indonesian adolescents remains a serious problem influenced by curiosity, identity formation, peer pressure, and the social environment. Smoking not only affects physical health but also impacts students’ psychological and academic development. This study aims to examine students’ smoking behavior before and after being taught behavioral contract techniques and to test the effectiveness of these techniques in reducing smoking behavior among students at SMK Negeri 4 Sigi. This study employs a quantitative approach using a quasi-experimental design with a one-group pre-test and post-test design. The study sample consisted of 10 tenth-grade students who had a smoking habit. The instrument used was a questionnaire consisting of 40 Likert-scale items that had been tested for validity and reliability. Data analysis employed the Wilcoxon Signed-Rank Test. The results indicated that students’ smoking behavior before the intervention was in the high category with an average of 3.9–4.1, whereas after the intervention, it was in the low category with an average of 1.8–2.0. Statistical test results showed a significance value of 0.005 < 0.05, indicating a significant difference between pre- and post-intervention levels. Thus, it can be concluded that the behavioral contract technique is effective in reducing students’ smoking behavior at SMK Negeri 4 Sigi.